Effect of temperature on the friction and wear behavior of electroless Ni–P–MoS2–CaF2 self-lubricating composite coatings. (December 2018) - Du, Sanming; Li, Zhen; He, Zhitao; Ding, Huiling; Wang, Xiaochao; Zhang, Yongzhen
Abstract: A Ni–P composite coating with MoS2 and CaF2 was prepared via electroless plating. The effect of temperature on the tribological behavior of the composite coatings was investigated. The results show that the tribological behavior of coatings largely depends on the temperature. The friction coefficient shows a decreasing trend with increasing temperature; the wear rate first decreases and then increases with increasing temperature. As the temperature increases from room temperature (RT) to 200 °C and 390 °C, the wear rate decreases by one order of magnitude compared to that at RT. The composite coating exhibits stable friction coefficient during the entire sliding in the temperature range of 200–570°C. Lubricating mechanisms were discussed. Highlights: A Ni–P–MoS2 –CaF2 self-lubricating coatings were prepared by electroless plating. The microstructural evolution of worn surface occurred with increasing temperature. The tribological properties of the coating depend greatly on the test temperatures.